Construction of a healthy lifestyle index using Italian National survey data - Scioni, Manuela; Baldan, Chiara; Ghirardo, Alessia; Boccuzzo, Giovanna (International Journal of Population Data Science, 2025)
Introduction Lifestyle choices encompassing dietary habits, physical activity levels, alcohol consumption, and tobacco use have been consistently shown to significantly impact individual health outcomes and overall well-being. Objectives This study proposes a novel composite index to measure the adoption of healthy lifestyles among the Italian population aged 18 years and over. Methods The Healthy Lifestyle Composite Index (HLCI) is constructed by aggregating four key dimensions: diet, physical activity, alcohol consumption, and tobacco use. The dimensions are structured as ordinal variables derived from the comprehensive Aspects of Daily Life (AVQ) multipurpose household survey conducted annually by the Italian National Statistical Institute (ISTAT). A formative approach is employed, involving defining the dimensions, determining weights through the Analytic Hierarchy Process based on expert evaluations, and specifying an aggregation procedure using a weighted Borda rule. Results The resulting HLCI provides a score from 0 to 100, with higher values indicating healthier lifestyles. Analysis of the HLCI and its dimensions using the 2022 AVQ data (n=32,600) reveals an average score of 61.77, with substantial variation across demographic groups. Descriptive analysis of the HLCI revealed significantly higher scores for females compared to males, driven by better performance in the alcohol and tobacco consumption dimensions. An inverted U-shaped trend emerged for age, with the youngest (18-19 years) and oldest (75+) groups exhibiting higher HLCI values. Educational level was positively associated with HLCI, with graduates scoring highest, excelling in physical activity. Geographically, the North-East region had the highest HLCI. Quantile regression on the first decile highlighted at-risk profiles with extremely low HLCI values, such as 35-44-year-old separated/divorced males with middle school education residing in South Italy. Conclusion Constructed using reliable data from an annually updated national survey, the HLCI allows for monitoring lifestyle dynamics across different demographic groups and geographic regions. The findings highlight specific segments of the population that may benefit from targeted interventions promoting a healthier lifestyle. 5 Bullet points: Proposal of a new Healthy Lifestyle Composite Index (HLCI) to measure adoption of healthy lifestyles in the Italian population. HLCI aggregates four dimensions: diet, physical activity, alcohol consumption, and tobacco use, using data from an annual national survey. HLCI employs a formative approach with expert-weighted dimensions and a weighted Borda aggregation rule to calculate the 0-100 score. Analysis of 2022 survey data shows average HLCI of 61.77 with variations across demographics like age, marital status, and educational level. Monitoring healthy lifestyle dynamics using regularly updated institutional data to target promotion efforts effectively.